Kemudahan Pendirian PT Perorangan melalui OSS Risk Based Approach sebagai Upaya Peningkatan Iklim Usaha - Zorya Kanoubie Attar Bakhri (Yayasan Al-Afif, 2025)
The Indonesian government, through Law Number 11 of 2020 on Job Creation, introduced a policy to simplify business licensing in order to improve the national business climate, including the implementation of the Online Single Submission Risk Based Approach (OSS RBA) system and the establishment of Single-Member Limited Liability Companies (PT Perorangan). This article aims to examine the mechanism for establishing PT Perorangan through OSS RBA and to analyze the implications of licensing facilitation on the improvement of the business climate. This study employs a normative juridical research method using statutory and conceptual approaches. The data used are secondary data obtained through library research, including legislation, legal literature, and relevant scholarly works. The analysis shows that the establishment of PT Perorangan through OSS RBA is conducted electronically through a simplified procedure based on the level of business risk, providing legal certainty for Micro and Small Enterprises (MSEs). Furthermore, the licensing facilitation offered by OSS RBA encourages business formalization, expands access to financing and legal protection, and supports the improvement of Indonesia’s business climate. Therefore, OSS RBA functions not only as an administrative tool but also as a strategic legal policy instrument to support sustainable economic growth and employment development.